Tailored second harmonic generation inTi-diffused PPLN waveguides usingmicro-heaters - Babai-Hemati, Jonas; vom Bruch, Felix; Herrmann, Harald; Silberhorn, Christine (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Nanosecond gating of superconducting nanowire single-photon detectors using cryogenic bias circuitry - Hummel, Thomas; Widhalm, Alex; Höpker, Jan Philipp; Jöns, Klaus; Chang, Jin; Fognini, Andreas; Steinhauer, Stephan; Zwiller, Val; Zrenner, Artur; Bartley, Tim (Optics Express)
Superconducting nanowire single-photon detectors (SNSPDs) show near unity efficiency, low dark count rate, and short recovery time. Combining these characteristics with temporal control of SNSPDs broadens their applications as in active de-latching for higher dynamic range counting or temporal filtering for pump-probe spectroscopy or LiDAR. To that end, we demonstrate active gating of an SNSPD with a minimum off-to-on rise time of 2.4 ns and a total gate length of 5.0 ns. We show how the rise time depends on the inductance of the detector in combination with the control electronics. The gate window is demonstrated to be fully and freely, electrically tunable up to 500 ns at a repetition rate of 1.0 MHz, as well as ungated, free-running operation. Control electronics to generate the gating are mounted on the 2.3 K stage of a closed-cycle sorption cryostat, while the detector is operated on the cold stage at 0.8 K. We show that the efficiency and timing jitter of the detector is not altered during the on-time of the gating window. We exploit gated operation to demonstrate a method to increase in the photon counting dynamic range by a factor 11.2, as well as temporal filtering of a strong pump in an emulated pump-probe experiment.
Keywords: Atomic and Molecular Physics; and Optics

Control of the electron dynamics in solid-state high harmonic generation on ultrafast time scales by a polarization-skewed laser pulse - Song, Xiaohong; Yang, Shidong; Wang, Guifang; Lin, Jianpeng; Wang, Liang; Meier, Torsten; Yang, Weifeng (Optics Express)
Since high-order harmonic generation (HHG) from atoms depends sensitively on the polarization of the driving laser field, the polarization gating (PG) technique was developed and applied successfully to generate isolated attosecond pulses from atomic gases. The situation is, however, different in solid-state systems as it has been demonstrated that due to collisions with neighboring atomic cores of the crystal lattice strong HHG can be generated even by elliptically- and circularly-polarized laser fields. Here we apply PG to solid-state systems and find that the conventional PG technique is inefficient for the generation of isolated ultrashort harmonic pulse bursts. In contrast, we demonstrate that a polarization-skewed laser pulse is able to confine the harmonic emission to a time window of less than one-tenth of the laser cycle. This method provides a novel way to control HHG and to generate isolated attosecond pulses in solids.
Keywords: Atomic and Molecular Physics; and Optics

Demonstration of Hong-Ou-Mandel interference in an LNOI directional coupler - Babel, Silia; Bollmers, Laura; Massaro, Marcello; Luo, Kai Hong; Stefszky, Michael; Pegoraro, Federico; Held, Philip; Herrmann, Harald; Eigner, Christof; Brecht, Benjamin; Padberg, Laura; Silberhorn, Christine (Optics Express)
Interference between single photons is key for many quantum optics experiments and applications in quantum technologies, such as quantum communication or computation. It is advantageous to operate the systems at telecommunication wavelengths and to integrate the setups for these applications in order to improve stability, compactness and scalability. A new promising material platform for integrated quantum optics is lithium niobate on insulator (LNOI). Here, we realise Hong-Ou-Mandel (HOM) interference between telecom photons from an engineered parametric down-conversion source in an LNOI directional coupler. The coupler has been designed and fabricated in house and provides close to perfect balanced beam splitting. We obtain a raw HOM visibility of (93.5 ± 0.7) %, limited mainly by the source performance and in good agreement with off-chip measurements. This lays the foundation for more sophisticated quantum experiments in LNOI.
Keywords: Atomic and Molecular Physics; and Optics

Fiber-coupled plug-and-play heralded single photon source based on Ti:LiNbO3 and polymer technology - Kießler, Christian; Conradi, Hauke; Kleinert, Moritz; Quiring, Viktor; Herrmann, Harald; Silberhorn, Christine (Optics Express)
A reliable, but cost-effective generation of single-photon states is key for practical quantum communication systems. For real-world deployment, waveguide sources offer optimum compatibility with fiber networks and can be embedded in hybrid integrated modules. Here, we present what we believe to be the first chip-size fully integrated fiber-coupled heralded single photon source (HSPS) module based on a hybrid integration of a nonlinear lithium niobate waveguide into a polymer board. Photon pairs at 810 nm (signal) and 1550 nm (idler) are generated via parametric down-conversion pumped at 532 nm in the LiNbO3 waveguide. The pairs are split in the polymer board and routed to separate output ports. The module has a size of (2 × 1) cm^2 and is fully fiber-coupled with one pump input fiber and two output fibers. We measure a heralded second-order correlation function of g_h(2)=0.05 with a heralding efficiency of η_h=3.5% at low pump powers
Keywords: Atomic and Molecular Physics; and Optics

Lithium niobate waveguide squeezer with integrated cavity length stabilisation for network applications - Stefszky, M.; vom Bruch, F.; Santandrea, M.; Ricken, R.; Quiring, V.; Eigner, C.; Herrmann, H; Silberhorn, C (Optics Express)
We report a titanium indiffused waveguide resonator featuring an integrated electro-optic modulator for cavity length stabilisation that produces close to 5 dB of squeezed light at 1550 nm (2.4 dB directly measured). The resonator is locked on resonance for tens of minutes with 70 mW of SH light incident on the cavity, demonstrating that photorefraction can be mitigated. Squeezed light production concurrent with cavity length stabilisation utilising the integrated EOM is demonstrated. The device demonstrates the suitability of this platform for squeezed light generation in network applications, where stabilisation to the reference field is typically necessary.
Keywords: Atomic and Molecular Physics; and Optics

All optical operation of a superconducting photonic interface - Thiele, Frederik; Hummel, Thomas; McCaughan, Adam N.; Brockmeier, Julian; Protte, Maximilian; Quiring, Victor; Lengeling, Sebastian; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optics Express)
Quantum photonic processing via electro-optic components typically requires electronic links across different operation environments, especially when interfacing cryogenic components such as superconducting single photon detectors with room-temperature control and readout electronics. However, readout and driving electronics can introduce detrimental parasitic effects. Here we show an all-optical control and readout of a superconducting nanowire single photon detector (SNSPD), completely electrically decoupled from room temperature electronics. We provide the operation power for the superconducting detector via a cryogenic photodiode, and readout single photon detection signals via a cryogenic electro-optic modulator in the same cryostat. This method opens the possibility for control and readout of superconducting circuits, and feedforward for photonic quantum computing.
Keywords: Atomic and Molecular Physics; and Optics